Evaluation of sorghum, sudan-grass and pearl millet cultivars in Manawatu - Millner JP; Silungwe D; McGill CR (Agronomy Society of New Zealand, 2013)
Sorghum, sudan-grass and pearl millet are versatile summer forages able to be grazed or conserved as silage. However, there is little recently published information on the performance these crops in New Zealand. A trial was carried out at Massey University, Palmerston North, to compare forage yields and crop morphology of four sorghum x sudan-grass hybrids (Pac 8421, Pac 8423, Pacific BMR and Bettagraze), two sudan-grass (Superdan 2 and Sprint) and one pearl millet (Nutrifeed) cultivars sown on the 8 and 21 December 2009. At final harvest, 57 and 58 days after sowing for the first and second sowing dates respectively, dry matter yields decreased (P<0.005) with delayed sowing from 12,792 kg ha-1 to 11,356 kg ha-1. There were cultivar differences (P<0.0001) at both sowing dates. Mean yields (across sowing dates) ranged from 9,823 (Nutrifeed) to 13,953 kg DM ha-1 (Pac 8423). There was a significant interaction (P<0.0001) between sowing date and cultivar for yield at the second harvest; cultivar differences for the first sowing date were larger than for the second, which suffered more from cool autumn temperatures. There was a strong, positive, linear relationship between plant height at harvest and DM yield (R2 = 0.69). Mean leaf:stem ratio, for the first sowing (1.9), was significantly (P<0.001) higher than in the second sowing (1.8) and was influenced by cultivar.
Keywords: 0703 Crop and Pasture Production